Electronic state dependence of heterogeneous electron transfer: injection from the S1 and S2 state of phlorin into TiO2. Issue 12 (28th March 2015) - Nieto-Pescador, Jesus; Abraham, Baxter; Pistner, Allen J.; Rosenthal, Joel; Gundlach, Lars
<x xml:space="preserve">Abstract</x> Similar heterogeneous electron transfer times, from different electronic states of a porphyrinoid into TiO2, suggest that the transfer process involve intermediate transition states not directly related to the steady bulk or surface density of states.